Sixty years of the first studies by Horácio Martins Canelas on Wilson's disease - Egberto Reis Barbosa; Jacy Bezerra Parmera; Rubens Gisbert Cury; Eduardo Luiz Rachid Cançado; Patrícia Áurea Andreucci Martins Bonilha; Hélio Afonso Ghizoni Teive (Arquivos de Neuro-Psiquiatria)
Research into Wilson's disease (WD) in Brazil had the effective participation of Professor Horácio Martins Canelas, from the Neurologic Clinic of the Teaching Hospital of the School of Medicine of Universidade de São Paulo (USP). His exponential contributions to the study of WD placed Brazil on the international stage, making USP's Neurologic Clinic one of the world's leading research centers in the area of neurodegenerative diseases with metal accumulation.